A Study on Calcination Parameters for Co-based Fischer-Tropsch Nanocatalyst - Mohamad Rizal bin Budin, Mohamad Rizal (Universiti Teknologi Petronas, 2010)

(untitled)
Calcination parameters for Co-based Fischer-Tropsch nanocatalyst is discussed in this project where the potential of alumina and silica supported cobalt catalysts for Fischer- Tropsch (FT) is studied. The objectives of the project is to first study the catalyst design and parameters of calcinations process, secondly to produce catalysts of different properties by manipulating the calcinations parameters and lastly to come out with the best parameter condition for calcination process for Co-based Fischer-Tropsch process based on the parameters taken into account. Using the wet impregnation method cobalt on alumina and cobalt on silica catalysts were prepared with 300 C, 400 C and 500 C calcinations temperature, producing altogether 6 samples. The samples are characterized by different methods including: Temperature Programmed Reduction, X-ray Diffraction and X-ray photoelectron spectroscopy. The performances of the catalysts were assessed and compared between those two supports and different calcinations temperature. From TPR results, both supports exhibit at 300 C calcined samples, reduced at lower temperature compared to 400 C and 500 C. In term of support, Cobalt on Alumina comes out to be structurally crystalline compared to amorphous Cobalt on Silica based on XRD result. XPS shows that the temperature reduction on about the same point for both support although more noise detected on Cobalt on Silica. Overall, Cobalt on Alumina appears preferable in comparison with silica support while some results came out unaffected by temperature changes. Details of the experiments are discussed further in the paper.